2002
DOI: 10.1016/s0378-3839(02)00090-x
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of sand waves after dredging

Abstract: Sand waves are large bed waves on the seabed, being a few metres high and lying hundreds of metres apart. In some cases, these sand waves occur in navigation channels. If these sand waves reduce the water depth to an unacceptable level and hinder navigation, they need to be dredged. It has been observed in the Bisanseto Channel in Japan that the sand waves tend to regain their shape after dredging. In this paper, we address modelling of this regeneration of sand waves, aiming to predict this process. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 29 publications
4
66
0
2
Order By: Relevance
“…The results show that the response of the system is such that it returns to its original state. These findings agree, at least qualitatively, with field observations (BOERS, 2005;KNAAPEN and HULSCHER, 2002;PATTIARATCHI and HARRIS, 2002). Thus, the system does not tend to a new equilibrium, which might have been expected in such a highly nonlinear system.…”
Section: Utrecht Modelsupporting
confidence: 81%
See 1 more Smart Citation
“…The results show that the response of the system is such that it returns to its original state. These findings agree, at least qualitatively, with field observations (BOERS, 2005;KNAAPEN and HULSCHER, 2002;PATTIARATCHI and HARRIS, 2002). Thus, the system does not tend to a new equilibrium, which might have been expected in such a highly nonlinear system.…”
Section: Utrecht Modelsupporting
confidence: 81%
“…Amplitude-Evolution Model KNAAPEN and HULSCHER (2002) developed a model to predict the regeneration of sand waves after dredging. Based on the findings of KOMAROVA and NEWELL (2000), they assumed that the growth of sand waves is described by the Landau equation.…”
Section: Behavior-oriented Modelsmentioning
confidence: 99%
“…그러나 이 연구들은 단 빔음향측심기 또는 천부탄성파 자료를 통한 2차적인 연구로 제한되었으며, 실질적인 층면구조를 파악하기 위한 기술적 한계를 가지고 있다. 그러나 최근 십여 년 동안 고정밀 위치정보 시스템과 함께 고정밀 다 중빔음향측심기술이 해저지형 연구에 많이 적용되었 다 (Knappen and Hulscher, 2002;Wienberg et al, 2004;Wienberg and Hebbln, 2005;Thornton et al, 2006;Kubicki et al, 2007;Li and King, 2007;Stockmann et al, 2009 (Flemming, 1988). (Fig.…”
Section: 서 론unclassified
“…Sand waves tend to regain their shape after dredging (Katoh and Kume 1998). Using an amplitude-evolution model based on the Landau equation, Knaapen and Hulscher (2002) were able to model this regeneration process correctly and concluded that the 4 application of their procedure was an important step for the optimisation of the maintenance dredging.…”
Section: Introductionmentioning
confidence: 99%